Perbedaan Perilaku Auditor dalam Situasi Konflik Audit Dilihat dari Segi Gender: Peran Locus of Control, Komitmen Profesi, dan Kesadaran Etis - Tuban Drijah Herawati; Sari Atmini (Jurusan Manajemen Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2010)
The objectives of this study are to empirically examine: 1) the interaction effect between personality variables (locus of control, professional commitments, and gender) and cognitive style variables (ethical awareness) to auditors’ reactions in audit conflict situations, 2) whether there are differences in the interaction effect between locus of control and ethical awareness to auditors’ reactions in audit conflict situations between male and female auditors, and 3) whether there are differences in the interaction effect between professional commitments and ethical awareness to auditors’ reactions in audit conflict situations between male and female auditors. This research used 39 auditors working in audit firm located in Surabaya and Malang as respondents. Data were analyzed using multiple regression analysis. The results of this research show that gender affect auditors’ response in audit conflict situations and that there is an interaction between gender and ethical awareness to auditors’ response in audit conflict situations. On the contrary, this research could not find any interactions between locus of control and ethical awareness. This research could not find any interactions between professional commitments and ethical awareness to auditors’ response in audit conflict situations either. Nevertheless, for female auditor sub sample, this research succeeded in finding interaction between locus of control and ethical awareness to auditors’ response in audit conflict situations.Keywords: locus of control, professional commitments, ethical awareness, gender, audit conflict situations